Kolaborasi Multi Pihak dalam Pelayanan Pemadam Kebakaran untuk Mengurangi Risiko Kebakaran di Kabupaten Gresik - Nanang Sujianto; Ika Devy Pramudiana; Nihayatus Sholichah; Dandy Patrija W (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study highlights the importance of multi-stakeholder collaboration in fire prevention and extinguishing services to reduce fire risks in Gresik Regency, Indonesia. The increasing fire threats due to industrialization, dense settlements, and environmental factors require a holistic approach involving the government, private sector, community, NGOs, and academia. Social capital theory is used as the theoretical framework, emphasizing the importance of trust, networks, and reciprocity in facilitating cooperation among actors. Strong social capital enhances coordination, information sharing, and collective action, thus strengthening community resilience to fire risks. Despite technology and digital platforms offering opportunities for risk prediction and rapid response, challenges such as low digital literacy and infrastructure limitations remain obstacles. Regulations and legal frameworks, including Memorandums of Understanding (MoUs) and incentives, are also crucial to build trust among stakeholders. This study shows that the success of fire risk management in Gresik requires systemic collaboration from the entire social and environmental ecosystem. The development of integrated digital communication platforms and community education is key to strengthening early warning systems and response preparedness. Inclusive partnerships based on trust are essential to building a resilient community against fire risks in Gresik.